Crack Analysis of Polyoxymethylene Reinforce Glass Fibre Material on Locker Table - Nidhar, Ainun; Auberta, Genia; Dewi, Anissa Puspa; Heryana, Ghany (President University, 2024)
Polyoxymethylene (POM) is a type of thermoplastic that is frequently used in various industrial applications due to its good dimensional stability, corrosion resistance, and superior tensile strength. However, in certain applications such as locker tables, the weakness of this material is revealed in structural failures. This research uses the finite element simulation method to analyse the failure of a locker table exposed to a helical torsion spring. The main focus was on the fracture of the part connected to the helical torsion spring, a common problem in plastic material applications subjected to cyclic loading. Results showed that the fracture occurred at a stress level of 121.061 MPa, exceeding the yield strength value that should have been broken at 150 MPa. In addition, the analysis showed that the highest Von Misses stress occurred where the spring was located, exceeding the specified yield strength. Tensile tests showed the effect of ambient temperature on the tensile strength of the POM+25%GF material. The proposed solution through the development of an additional structure in the form of ribs on the product successfully increased the strength of the locker table under load. This research provides important insights in improving product design to minimise the risk of structural failure in POM+25%GF material.